EUS-guided fiducial placement for pancreatobiliary malignancies: safety, infection risk, and use of peri-procedural antibiotics - Chandnani, Madhuri; Faisal, Mir Fahad; Glissen-Brown, Jeremy; Sawhney, Mandeep; Pleskow, Douglas; Cohen, Jonah; Berzin, Tyler M. (Endoscopy International Open, 2020)
Background and study aims Chemoradiation with stereotactic body radiation therapy (SBRT) is increasingly being used for optimal treatment of locally advanced pancreatobiliary cancers. Fiducial markers are used to track these tumors during SBRT. Endoscopic ultrasound (EUS) is the preferred route for fiducial marker placement for ease of access to pancreatobiliary structures and accurate placement. Here we evaluate the safety and infection risk associated with EUS-guided fiducial placement for pancreatobiliary malignancies and use of peri-procedural prophylactic antibiotics.Patients and methods This was a retrospective, single-center study including consecutive patients presenting for EUS-guided fiducial placement in pancreatobiliary region by three expert interventional endoscopists for SBRT from July 2010 to February 2018 at a tertiary care center. Patient demographics, tumor characteristics, EUS technique, fiducials, use of prophylactic antibiotics, adverse events (AEs) and SBRT/Cyberknife administration were reported.Results A total of 355 patients with pancreatobiliary malignancy underwent EUS-guided fiducial placement, of whom 308 patients (86.76 %) successfully underwent SBRT. Of the patients, 304 (85.63 %) received peri-procedural prophylactic antibiotic. Of 355 total patients, 5.9 % (n = 21) were noted to develop AEs (mild to severe) with no significant difference in incidence of infection with or without use of peri-procedural prophylactic antibiotic. Only three patients developed infectious AEs, none of which were definitively related to fiducial placement.Conclusion EUS-guided fiducial placement for pancreatobiliary malignancy is safe and efficacious, and risk of infection is rare, regardless of whether or not peri-procedural antibiotics are used. We favor limiting routine use of peri-procedural antibiotics for patients undergoing EUS-guided fiducial placement in pancreaticobiliary malignancy.